Digital rural construction and agricultural green total factor productivity: the role of land finance, land resource misallocation, and agricultural technology innovation - Zhang, Zhenyang; Hu, Tianxiang; He, Jinghui (Frontiers in Environmental Science, 2025)
Prior studies on whether and how digital rural construction (DRC) contributes to enhancing agricultural green total factor productivity (AGTFP) remain limited. This study uses Difference-in-Differences method and panel data comprising 18,543 observations from 2,128 counties (districts) between 2012 and 2022 to examine the impact of DRC on AGTFP and its underlying mechanisms. The findings indicate that DRC significantly boosts AGTFP, a result that holds after conducting several robustness checks and endogeneity test, including replacing the dependent variable, excluding other policy impacts, adjusting the sample period, and propensity score matching method. The mechanisms through which DRC enhances AGTFP include improving land finance, alleviating land resource misallocation, and fostering agricultural technology innovation. The effects of DRC on AGTFP are notably more pronounced in the central and western regions of China, non-major grain-producing areas, and regions with lower land transfer efficiency. Our insights clarify the influence pathways through which DRC facilitates the enhancement of AGTFP, offering fresh theoretical insights and practical implications for further guiding DRC and leveraging the efficiency of AGTFP.